2016
DOI: 10.46867/ijcp.2016.29.00.09
|View full text |Cite
|
Sign up to set email alerts
|

Responses to Familiar and Unfamiliar Humans by Belugas (Delphinapterus leucas), Bottlenose Dolphins (Tursiops truncatus), & Pacific White-Sided Dolphins (Lagenorhynchus obliquidens): A Replication and Extension

Abstract: Previous research has documented that cetaceans can discriminate between humans, but the process used to categorize humans still remains unclear. The goal of the present study was to replicate and extend previous work on the discrimination between familiar and unfamiliar humans by three species of cetaceans. The current study manipulated the familiarity and activity level of humans presented to 12 belugas (Delphinapterus leucas) housed between two facilities, five bottlenose dolphins (Tursiops truncatus), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
(70 reference statements)
0
3
0
Order By: Relevance
“…In an extension to that study in captivity, Hill, Yeater et al (2016) also found that belugas looked longer at unfamiliar humans, regardless of their clothing (standardized or uniforms). The captive belugas also exhibited a longer gaze duration for active humans rather than stationary ones.…”
Section: Direction and Duration Of Gazementioning
confidence: 68%
See 1 more Smart Citation
“…In an extension to that study in captivity, Hill, Yeater et al (2016) also found that belugas looked longer at unfamiliar humans, regardless of their clothing (standardized or uniforms). The captive belugas also exhibited a longer gaze duration for active humans rather than stationary ones.…”
Section: Direction and Duration Of Gazementioning
confidence: 68%
“…That inference that has been supported by follow-up studies conducted in captivity. When studying 12 belugas across multiple zoological facilities both Yeater et al (2014) and Hill, Yeater et al (2016) found lateralized eye preferences at the individual level. In an extension of this line of research, Guarino et al (2017) and Yeater et al (2017) found that belugas tended to view both familiar and novel objects using both eyes, but that they demonstrated a left eye preference when monocular vision was used.…”
Section: Lateralitymentioning
confidence: 98%
“…Again, "same" here does not mean identical, but the same relative to the claim and experimental unit at hand. For example, consider a researcher who wants to compare the relative response of dolphins (e.g., Hill et al, 2016) to familiar and unfamiliar humans with that of elephants (e.g., Polla et al, 2018). Clearly, the researcher must sample from different populations of experimental units [dolphins, elephants], and a different population of settings [aquatic, non-aquatic].…”
Section: Species-fair Comparisonsmentioning
confidence: 99%